Evaluation of Primary School Inclusive Education Curriculum Based on Context, Input, Process, and Product (CIPP) Model - Indrianto, Nino; Nurdin, Arbain (Letiges, 2024)
This research aims to provide a descriptive overview of the results of the analysis regarding the suitability of inclusive education curriculum and to evaluate the impact on MI Al-Ma'arif 02 Jombang Jember and SD Al-Irsyad Al-Islamiyah Jember based on the CIPP model, as well as a comparison between these two institutions. The approach used is a qualitative approach with a multicase study method. Informant selection was done using a purposive technique. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted using the Miles, Huberman, and Saldana model, which involves data condensation, data presentation, verification, and conclusion drawing. The study results show that these two elementary educational institutions have similarities and differences related to the suitability of the inclusive education curriculum that the institutions have implemented based on the program evaluation model, namely the CIPP model. Similarities are found in the context and product aspects. Meanwhile, differences can be found in the input aspect because the madrasah still needs accompanying teachers and inadequate infrastructure. Then in the process aspect, it was found that elementary schools implement more diverse learning models based on the abilities and characteristics of students with special needs. It should be noted that this research is limited to aspects of the inclusive education curriculum at the basic education level. The findings of this research method provide originality in the form of the CIPP model which can be used as a case study analysis approach. Scientifically, by evaluating the educational curriculum, these findings provide a lot of input for improving education in the future, especially in inclusive education.